THE INFLUENCE OF TRUST AND PERSONAL SELLING ON CUSTOMER LOYALTY IN SETYA SHOP SIDOARJO MSMEs - Ludiro, Galih; Fullchis Nurtjahjani; M Mustofa Hadi (CV. Radja Publika, 2024)
Setya shop is an individual company that sells 3Kg LPG, the company's success is motivated by several factors including customer loyalty, trust and personal selling, the purpose of this study is to test and analyse the effect of trust and personal selling simultaneously on customer loyalty at MSMEs Setya shop Sidoarjo. This research method is quantitative. The scope of this study uses two independent variables of trust (X1) and Personal Selling (X2) and the dependent variable used is customer loyalty at MSMEs Setya shop in Sidoarjo (Y). In this study, the population is customers of MSMEs Setya shop who make purchases at least once offline as many as 600 people/customers. The sample calculation in this study uses the Slovin formula with a significance rate of 10%. Therefore, this study has a sample size of 120 customers of Setya shop. In particular, this study used Simple Random Sampling. Data collection using a questionnaire with a Likert scale. Data analysis using multiple linear regression analysis and hypothesis testing consisting of t test, F test and coefficient of determination. The results concluded that there is a simultaneous influence of trust and personal selling on customer loyalty in MSMEs Setya shop Sidoarjo. This means that trust and personal selling are needed to create and increase customer loyalty at Setya shop Sidoarjo.